A NEW METHOD FOR CALCULATING THE ROVIBRATIONAL STATES OF POLYATOMICS WITH APPLICATION TO WATER DIMER - Althorpe, S; Clary, D (1995)
A new method is developed for calculating the lowest few rovibrational states of polyatomic molecules, using the discrete variable representation (DVR). The method is an extension to the diagonalization-truncation procedure which has been used in most DVR calculations to date. It starts with a set of functions which approximately describe the wave function at a set of DVR points, and adds corrections to them by using variation-perturbation theory. This is done iteratively, after the manner of the recently developed iterative secular equation (ISE) method of Slee and LeRoy. This new "DVR-ISE" method can be successfully applied to molecules whose dynamics involve strong coupling between all degrees of freedom. To demonstrate this it is applied to (H 2O)2 in calculations of the lowest few energy levels for intermolecular angular motion. Better convergence is obtained than was found possible in conventional finite basis calculations on the same system. © 1995 American Institute of Physics.